Tanggung Jawab Orang Tua dalam Pendidikan Islam Menurut Al-Qur’an - Maulana, Iqbal; Salminawati, Salminawati; Dahlan, Zaini (Jayapangus Press, 2025)
Education serves as the fundamental pillar in shaping children’s character and spirituality, with parents playing a central role in Islamic teachings. The Qur’an provides clear guidance on the importance of education grounded in monotheism (tauhid), morality, and knowledge, as reflected in Q.S. An-Nisa’ [4]: 9, Q.S. Luqman [31]: 13–19, and Q.S. At-Tahrim [66]: 6. This study aims to analyze the concept of parental responsibility in Islamic education based on these three verses and to explore their relevance in addressing contemporary challenges in family-based education. The research employs a qualitative method using library research and a thematic (maudhu’i) interpretation approach to extract both thematic and contextual meanings from the selected verses. The findings reveal that the Qur’an places parents as the primary and foremost educators, responsible for nurturing their children’s faith, morals, and life skills as provisions for both this world and the hereafter. In the modern context, this role faces serious challenges, including work-related busyness, secular cultural influences, and value disruption due to digital media. The study concludes that family-based education rooted in the Qur’an remains highly relevant and essential as a moral safeguard for children amid an era of rapid change. The implementation of Qur’anic education values centered on monotheism, moral guidance, and parental role modeling is key to forming a generation of Muslims who are faithful, intelligent, and morally upright.